A water/cottonseed oil bath with controllable dye sorption for high dyeing quality and minimum discharges. (1st November 2019) - Mu, Bingnan; Liu, Linyun; Li, Wei; Yang, Yiqi
Abstract: We developed a clean reactive dyeing system for industrialization by controlled demulsification of the dyeing medium containing cottonseed oil. Low dye fixation and high pollution are the major problems of conventional aqueous reactive dyeing. Current alternative dyeing technologies have their deficiencies such as undesired dyeing quality and toxic discharges. Semi-stable emulsion dyeing could achieve high levelness and fixation of dyes by adjusting the demulsification speed of dyeing medium and water content in the system on a pilot scale. Compared to aqueous dyeing, up to 47% dyes could be saved to obtain the same shade in semi-stable emulsion dyeing. Dyeing levelness of emulsion dyeing has no significant difference from that of aqueous dyeing. Dye discharge using the semi-stable emulsion system was reduced by 90%. Discharges of salt and dispersing agents were eliminated. More than 99.8% of cottonseed oil could be recycled. Graphical abstract: Image 1 Highlights: High dyeing properties are achieved using unstable emulsion for warm reactives. Dyeing levelness and fixation is adjusted by demulsification in dyeing medium. Discharges are reduced by 96.5% and no salt is used. Degradable cottonseed oil can be easily removed from fabric after dyeing. A pilot-scale dyeing unit demonstrated the high industrial feasibility.